Pengelolaan Digital PR melalui Instagram @dishut_jabar - Permana, Bima Fauzi; Sumadiria, Haris; Cholidah, Lida Imelda (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2024)
This study aims to find out how digital PR is managed on Instagram @dishut_jabar through the concept of The Circullar Model of Some for Social Communication from Regina Luttrell. This study used a qualitative descriptive method with collection techniques through in-depth interviews, observation, and documentation studies. The research results obtained are; 1) the stage of sharing: conducting observations and surveying data for processing; 2) optimizing stage: conducting media screening and improving the quality of work; 3) managing stage: conducting media monitoring for information management through the insight feature on Instagram, then providing quick responses to the public; 4) the engage stage: holding joint activities with the public and involving influencers who have public influence.